The Natural History of Untreated Biopsy Grade Group Progression and Delayed Definitive Treatment for Men on Active Surveillance for Early-Stage Prostate Cancer. Issue 5 (4th May 2022) - Chappidi, Meera R.; Bell, Alexander; Cowan, Janet E.; Greenberg, Scott A.; Lonergan, Peter E.; Washington, Samuel L.; Nguyen, Hao G.; Shinohara, Katsuto; Cooperberg, Matthew R.; Carroll, Peter R.
Abstract : Purpose: For men with clinically localized prostate cancer outcomes of continuing active surveillance (AS) after biopsy progression are not well understood. We aim to determine the impact of continuing AS and delayed definitive treatment after biopsy progression on oncologic outcomes. Materials and Methods: Participants in our prospective AS cohort (1990–2018) diagnosed with grade group (GG) 1, localized prostate cancer, with prostate specific antigen <20 who were subsequently upgraded to ≥GG2, and underwent further surveillance (biopsy/imaging/prostate specific antigen) were identified. Patients were stratified by post-progression followup into 3 groups: continue AS untreated, pursue early radical prostatectomy (RP) ≤6 months, or undergo late RP within 6 months to 5 years of progression. Patients receiving other treatments were excluded. We compared characteristics between groups and examined the associations of early vs late RP with risk of adverse pathology (AP) at RP and recurrence-free survival (RFS) after RP. Results: Of 531 patients with biopsy progression and further surveillance 214 (40%) remained untreated, 192 (36%) pursued early RP and 125 (24%) underwent late RP. Among patients who underwent early vs late RP, there was no difference in GG (p=0.15) or AP (55% vs 53%, p=0.74) rate at RP, or 3-year RFS (80% vs 87%, log-rank p=0.64) after RP. In multivariable models, only Cancer of Prostate Risk Assessment post-surgical score was associated with risk of RFS (HR=1.42 per point, 95% CI 1.24–1.64). Conclusions: Among patients continuing AS after biopsy progression, 60% underwent surgery within 5 years. Delayed surgery after progression was not associated with higher risk of AP or RFS. This suggests select patients may be able to safely delay treatment after progression.